Climate Change Communication Strategies On Social Media: A Case Study Of Youth Activist Environmental Campaigns - Zulfikar Arahman; Dian Rianita; Suroso Suroso; Razia Khan (Yayasan Adra Karima Hubbi, 2025)
Background. The proliferation of social media has fundamentally reshaped public discourse, creating powerful new arenas for climate change communication. Youth activists, in particular, have adeptly leveraged these platforms to mobilize global environmental campaigns, bypassing traditional media gatekeepers. This research addresses the need to understand the specific communication strategies employed by these digital-native activists to engage audiences and drive collective action. Purpose. This study aims to identify and analyze the primary communication strategies used by youth-led environmental campaigns on social media platforms. Method. Adopting a qualitative case study approach, this research conducts a content analysis of social media posts from prominent youth activist campaigns across Instagram, X (formerly Twitter), and TikTok. The analysis focuses on message framing, narrative techniques, visual elements, and calls to action. Results. The findings reveal a multi-faceted communication strategy that combines strong emotional appeals and personal storytelling with the simplification and visualization of complex scientific data. Furthermore, a consistent and clear call to action, often linked to specific policy demands or lifestyle changes, is a central component of these campaigns. Conclusion. This study concludes that the effectiveness of youth-led climate campaigns on social media lies in their ability to create a relatable, urgent, and empowering narrative that fosters a sense of shared identity and collective efficacy among their followers.